3D-QSAR Study on a Series of VEGFR-2 Kinase Inhibitors: 3-Pyrrole Substituted Indolin-2-Ones Compounds - Shunlai Li; Rutao Zhang; Hongguang Du (Journal of Chemistry)
The vascular endothelial growth factor receptor-2 kinases (VEGFR-2) are attractive targets for the development of anticancer agents. Self-organizing molecular field analysis (SOMFA) (a simple three-dimensional quantitative structure-activity relationship (3D-QSAR) method) is used to study the structure-activity correlation of 3-pyrrole substituted indolin-2-ones VEGFR-2 inhibitors. The statistical results, cross-validated (0.5267) and non-cross-validated (0.5623), show a reliable predictive ability. The contributions of shape and electrostatic fields are 42.7% and 57.3%, respectively. Analysis of SOMFA models through shape and electrostatic grids provide useful information for the design and optimization of new 3-pyrrole substituted indolin-2-one based VEGFR-2 inhibitors.